FACTORS THAT INFLUENCE CORPORATE TURNAROUND COMPANIES THAT HAVE FINANCIAL DISTRESS WITH OPERATIONAL INCOME AS A MODERATING VARIABLE (EMPIRICAL STUDY IN MANUFACTURING COMPANIES LISTED ON BEI IN PERIOD OF 2008-2017) - Saragi, Dame Ria Rananta (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to examine factors that can affect the ability of companies that are experiencing financial distress to be able to do corporate turnaround so that companies can return to financial health. The factors tested in this study were Severity, Firm Size, Free Assets, Asset Retrenchment, Expense Retrenchment, and CEO Substitution. The population in this study were 61 manufacturing companies listed on the Indonesia Stock Exchange for 10 years, starting from 2008 to 2017 and based on the criteria of all companies selected through purposive sampling method as a sample in this study. Based on the results of testing the statistical value shows that the data used in this study matches the model and the results of the suitability test of the statistical value model show the model used in this study is able to analyse the problem in the study. Partially, the results of statistical tests show that Free Assets and Expense Retrenchment affect the ability of companies in financial distress when conducting corporate turnaround. Whereas Severity, Company Size, Retrenchment Asset and CEO Turnover cannot affect the ability of companies in financial distress when conducting corporate turnaround and Operational Income cannot moderate the effect of Severity, Company Size, Free Asset, Asset Retrenchment, Expense Retrenchment and CEO Turnover on Corporate Turnaround. Simultaneously based on the F (F-statistical) test, all variables namely Severity, Firm Size, Free Assets, Asset Retrenchment, Expense Retrenchment and CEO Turnover can affect the ability of companies to conduct corporate turnaround.